1992
DOI: 10.1007/bf01537898
|View full text |Cite
|
Sign up to set email alerts
|

Perceived attachments to parents and peers and psychological well-being in adolescence

Abstract: This paper reports the findings from a study of 935 adolescents' perceived attachments to their parents and peers, and their psychological health and well-being. Perceived attachment to parents did not significantly differ between males and females. However, females scored significantly higher than males on a measure of attachment to peers. Also, relative to males, they had higher anxiety and depression scores, suggesting poorer psychological well-being. Overall, a lower perceived attachment to parents was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
259
4
20

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 447 publications
(307 citation statements)
references
References 14 publications
24
259
4
20
Order By: Relevance
“…A high score on the overall attachment scale (range 10-40) indicates higher levels of child secure attachment towards the parents. The IPPA has shown to be a reliable and valid instrument 4,12,44 .…”
Section: Methodsmentioning
confidence: 99%
“…A high score on the overall attachment scale (range 10-40) indicates higher levels of child secure attachment towards the parents. The IPPA has shown to be a reliable and valid instrument 4,12,44 .…”
Section: Methodsmentioning
confidence: 99%
“…However, several measures had been used to assess different aspects of adolescent coping, and these were combined to form a stable latent variable. These measures included the Communication subscale of a shortened version of the Inventory of Parent and Peer Attachment (IPPA: Armsden & Greenberg, 1987;Nada Raja et al, 1992). Four items assessed perceived levels of communication with each of parents and peers, with items rated on a four-point Likert-type scale of 1 = almost never or never, 2 = sometimes, 3 = often, and 4 = almost always or always.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Given differences between adolescent boys and girls both in terms of experienced distress (Byrne & Mazanov, 2003;, coping behaviors (Nada Raja, McGee, & Stanton, 1992), and rates of smoking in NZ (Stanton, 1995), we also examine gender-based differences in the relationships between smoking and coping in later adulthood..…”
mentioning
confidence: 99%
“…Response categories ranged from 1 ¼ never to 4 ¼ almost always. Empirical research on the psychometric properties showed high internal consistencies (e.g., Armsden & Greenberg;Nada Raja, McGee, & Stanton, 1992). Furthermore, a high 3-week test-retest reliability has been reported, and the scale appears to possess convergent validity (Armsden & Greenberg).…”
Section: Parentingmentioning
confidence: 99%